LITERATUR REVIEW: TANTANGAN DAN STRATEGI GURU SEKOLAH DASAR DALAM PEMBELAJARAN BAHASA JAWA DI ERA DIGITAL - Wicaksono, Gigih; Eko Handoyo; Hanafi Hussin; Indriana Eko Armaidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Javanese language learning in elementary schools faces various challenges in the digital era, such as declining use of Javanese among students, low learning interest, the influence of gadget and social media use, limited learning media, and teacher readiness in utilizing digital technology. This study aims to analyze the challenges and strategies implemented by elementary school teachers in learning Javanese in the digital era through a Systematic Literature Review (SLR) approach. The study was conducted by collecting and analyzing relevant scientific articles published in 2022–2025. The selected articles were analyzed thematically to identify patterns, similarities, and differences related to challenges, learning strategies, and cultural preservation efforts in Javanese language learning. The results show that teachers face complex challenges in the form of low use of Javanese, especially krama and krama inggil (high Javanese), limited digital competency, lack of supporting facilities, and monotonous learning methods. However, teachers have begun to implement various innovative strategies such as the use of digital media in the form of YouTube, Quizizz, QuizWhizzer, TikTok, interactive PowerPoint, educational games, mobile learning, and culture-based learning approaches through wayang (wayang), tembang dolanan (traditional songs), and traditional games. This strategy has been proven to increase student motivation, participation, and interest in learning while supporting cultural preservation and character education. Therefore, teachers have a crucial role in balancing digital transformation with the preservation of local cultural values ​​in Javanese language learning. Pembelajaran Bahasa Jawa di sekolah dasar menghadapi berbagai tantangan pada era digital, seperti menurunnya penggunaan Bahasa Jawa di kalangan siswa, rendahnya minat belajar, pengaruh penggunaan gawai dan media sosial, keterbatasan media pembelajaran, serta kesiapan guru dalam memanfaatkan teknologi digital. Penelitian ini bertujuan untuk menganalisis tantangan dan strategi yang dilakukan guru sekolah dasar dalam pembelajaran Bahasa Jawa di era digital melalui pendekatan Systematic Literature Review (SLR). Penelitian dilakukan dengan mengumpulkan dan menganalisis artikel ilmiah relevan yang diterbitkan pada tahun 2022–2025. Artikel yang terpilih dianalisis secara tematik untuk mengidentifikasi pola, persamaan, dan perbedaan terkait tantangan, strategi pembelajaran, serta upaya pelestarian budaya dalam pembelajaran Bahasa Jawa. Hasil penelitian menunjukkan bahwa guru menghadapi tantangan kompleks berupa rendahnya penggunaan Bahasa Jawa, khususnya krama dan krama inggil, keterbatasan kompetensi digital, kurangnya sarana pendukung, serta metode pembelajaran yang monoton. Namun demikian, guru mulai menerapkan berbagai strategi inovatif seperti penggunaan media digital berupa YouTube, Quizizz, QuizWhizzer, TikTok, PowerPoint interaktif, permainan edukatif, mobile learning, serta pendekatan pembelajaran berbasis budaya melalui wayang, tembang dolanan, dan permainan tradisional. Strategi tersebut terbukti mampu meningkatkan motivasi, partisipasi, dan minat belajar siswa sekaligus mendukung pelestarian budaya dan pendidikan karakter. Oleh karena itu, guru memiliki peran penting dalam menyeimbangkan transformasi digital dengan pelestarian nilai budaya lokal dalam pembelajaran Bahasa Jawa.